Pulmonary interstitial glycogenosis cells express mesenchymal stem cell markers. Issue 4 (22nd October 2020) - Galambos, Csaba; Wartchow, Eric; Weinman, Jason P.; Abman, Steven H.
Pulmonary interstitial glycogenosis (PIG) was first defined as a distinct neonatal interstitial lung disease of unknown aetiology that presents in neonates and young infants with mild to severe hypoxic lung disease [1]. Characterised clinically by unexplained respiratory distress and cyanosis with an onset during early infancy, PIG was primarily defined by the presence of distinct and unusual-appearing cells contained within the interstitium that were characterised by a widened interstitium containing variable numbers of immature-appearing, polygonal-to-spindle shaped cells, which may contribute to impaired gas exchange. The most unique feature of PIG cells is the widespread presence of non-membrane bound, periodic acid-Schiff stain-positive, mono-particulate glycogen in the cytoplasm, for which the disease was named ("glycogenosis") [1]. By ultrastructure, PIG cells are considered primitive due to the presence of only sparse organelles and a lack of specific features that indicate differentiation towards any well-characterised pulmonary cell line, including lymphocytes or macrophages [1]. Pulmonary interstitial glycogenesis (PIG) is characterised by a unique but poorly characterised cell population in developmental lung disease. This study reports that PIG cells express cellular markers, suggesting a mesenchymal stem cell lineage. https://bit.ly/2YNdDIY